Linkage to Care Is Important and Necessary When Identifying Infections in Migrants - Pareek, Manish (Int J Environ Res Public Health, 2018)
Migration is an important driver of population dynamics in Europe. Although migrants are generally healthy, subgroups of migrants are at increased risk of a range of infectious diseases. Early identification of infections is important as it prevents morbidity and mortality. However, identifying infections needs to be supported by appropriate systems to link individuals to specialist care where they can receive further diagnostic tests and clinical management. In this commentary we will discuss the importance of linkage to care and how to minimise attrition in clinical pathways.